The Effects of Moving Load on the Hydroelastic Response of a Very Large Floating Structure. (3rd December 2018) - Zhu, Le; Shao, Fei; Xu, Qian; Sun, Yonggang; Ma, Qingna
Abstract : The hydroelastic response of a very large floating structure in regular waves suffering an external moving point load is considered. The linearized velocity potential theory is adopted to describe the fluid flow. To take into account the coupled effects of the structure deformation and fluid motion, the structure is divided into multiple segments and connected by an elastic beam. Then through adding a stiffness matrix arising from the elastic beam into the multiple bodies coupled motion equations, the hydroelastic response is considered. By applying the Fourier transform to the obtained frequency domain coefficients, the motion equation is transformed into the time domain and the external point load is further considered. The accuracy and effectiveness of the proposed method are verified through the comparison with experimental results. Finally, extensive results are provided, and the effects of the moving point load on the hydroelastic response of the very large floating structure are investigated in detail.